al-Fitri al-Tsaqafi; Nahwa al-Jadid fi al-Manhaj al-Kalami 'inda Muhammad al-Ghazali - Muhammad Shohibul Mujtaba (Tasfiyah: Jurnal Pemikiran Islam, 2019)
This research was written to see one of the new methods in the development of the science of kalam, by using the book Aqidah al-Muslim by Syaikh Muhammad al-Ghazzali as the object of research. The new method is al-Fithry al-Tsaqafi. From his book, it can be analyzed that Syaikh Muhammad al-Ghazali applied the method of al-Fithry al-Tsaqafi in the development of contemporary kalam science issues. This is illustrated from the five chapters in the book. Namely: Criticism of the science of kalam, proof of the form of God, creation of nature, description of the verse "laisa kamitslihi syai’un", and human freedom (af’āl al-ibād). From these observations, there are three main elements of how the author has actually used the method of al-Fithry al-Tsaqafi, this is evidenced by the following reasons: First, he tried to explain kalam problems with axiomatic things, so that the reader is not burdened with terms that are difficult to understand. Second, trying to build a creed from its immediate source, namely the Qur'an and Sunnah. Three, explaining the negative side of the previous method of the science of kalam and its influence with modern thought.